R&D for Quality Improvement and Network Externalities - Luca Lambertini; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
We investigate the bearings of network externalities on product quality improvements requiring costly R&D investments. The model considers the dynamic behaviour of a monopolist alternatively maximising profits or social welfare. On the one hand, we confirm much of the acquired wisdom from the static literature on the same topic, about the arising of quality undersupply at the private optimum. On the other, we identify the initial conditions that must be met for R&D activity to be observed under profit-seeking behaviour. We also show that the presence of network externalities affects the optimal behaviour of the profit-seeking firm but not that of a benevolent planner, who serves all consumers and smooths the R&D costs leading to a steady state quality which is independent of network concerns.
Keywords: 330; Monopol; Produktqualität; Netzwerkökonomik; Industrieforschung; Theorie